Evaluation of natural radioactivity levels and potential radiological hazards of common building materials utilized in Mediterranean region, Turkey - Karataşlı, Muhammet; Turhan, Şeref; Kurnaz, Aslı (Springer Science and Business Media LLC, 2021)
Abstract Radiometric measurement of building materials is very important to assess the internal and external exposure caused by the ionizing radiation emitted from terrestrial radionuclides in building materials. The activity concentrations of 226Ra, 232Th, and 40K in fifty-eight samples of fifteen different structural and covering building materials commonly used in Osmaniye province located in the Mediterranean region of Turkey were measured by using gamma-ray spectroscopy. The activity concentrations of 226Ra, 232Th and 40K varied from 2.5 ± 0.1 (marble) to 145.7 ± 4.4 (clay brick), 1.3 ± 0.1 (marble) to 154.3 ± 4.1 (marble) and 8.6 ± 0.2 (sand) to 1044.1 ± 70.3 (granite), respectively. Radiological parameters (activity concentration index, alpha index, indoor absorbed gamma dose rate and the corresponding annual effective dose rate, and excess lifetime cancer risk) were estimated to evaluate the health hazards associated with these building materials. Since the estimated values of these parameters are within the recommended safety limits or criteria values, the use of the studied building materials in the construction of dwellings can be considered to be safe for the residents of the region.
Keywords: Turkey; Construction Materials; Radiation exposure; Thorium; Potassium Radioisotopes; Gamma-ray spectrometry; Radiation Dosage; Spectrometry, Gamma; Radioactivity; Radiation Monitoring; . Effective dose; Cancer risk, Osmaniye; Radium; 13. Climate action; 11. Sustainability